2019
DOI: 10.26877/imajiner.v1i5.4467
|View full text |Cite
|
Sign up to set email alerts
|

Profil Pedagogical Content Knowledge (PCK) Calon Guru Matematika dalam Kesiapan Mengajar

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui profil kemampuan Pedagogical Content Knowledgecalon guru matematika dalam kesiapan mengajar. PCK sangat penting untuk evaluasi calon guru matematika.Penelitian ini merupakan penelitian deskriptif kualitatif dengan subjek penelitiannya adalah mahasiswa calon guru matematika yang terdiri dari 2 orang, sedang melakukan magang 3, mempunyai IPK diatas 3.00. Teknik pengumpulan data yang digunakan adalah observasi dan wawancara. Teknik analisis data dilakukan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Calon guru harus di bekali dengan kemampuan propfesional yang mempunyai keterampilan-ketrampilan yang mampu mempermudah siswa dalam pembelajaran. (Santosa, 2019).…”
Section: Pendahuluan *unclassified
“…Calon guru harus di bekali dengan kemampuan propfesional yang mempunyai keterampilan-ketrampilan yang mampu mempermudah siswa dalam pembelajaran. (Santosa, 2019).…”
Section: Pendahuluan *unclassified
“…Based on research conducted by Anindita (2018) in one of the private high schools in Yogyakarta on the topic of derivatives using the Discovery Based Learning strategy, it was found that the PCK skills of teachers still need to be improved because there are still PCK indicators that have not been met. Then the research conducted by Widyastuti (2019) related to the PCK profile of mathematics teachers in one of the private junior high schools in Sukabumi on the topic of quadrilateral using the Problem Based Learning learning model, and the research results obtained that the teacher's PCK ability was quite good because it was able to fulfill almost all PCK indicators.…”
Section: ▪ Introductionmentioning
confidence: 99%
“…Based on the problems that the author got through observations and previous research conducted by Anindita (2018), Widyastuti (2019), Sulistyarini (2020), the researcher will conduct research to answer the following questions: how to plan and implement a flipped classroom strategy in teaching compound event probability for Mathematics Education students who take Micro Teaching C class courses in the 2022/2023 academic year, and what is the pedagogical content knowledge (PCK) profile of Mathematics Education students who take Micro Teaching C class courses in the 2022/2023 academic year in designing and practicing flipped classroom learning strategies to teach a material at the high school level.…”
Section: ▪ Introductionmentioning
confidence: 99%
“…Calon guru harus di bekali dengan kemampuan mengajar yang mempunyai keterampilan-ketrampilan yang mampu mempermudah siswa dalam pembelajaran. Keterampilan-keterampilan tersebut di antaranya adalah mampu memanfaatkan media, lingkungan kelas, lembar kerja siswa dan mengaitkan karakter ke dalam pembelajaran (Santosa, Kusumaningsih, & Endahwuri, 2019) Penelitian Maryono (2016) mengungkapkan bahwa kenyataan di lapangan menunjukkan bahwa guru matematika secara umum bisa dikategorikan ke dalam 4 kelompok, yaitu: (1) guru dengan pengetahuan konten dan pengetahuan pedagogis yang baik; (2) guru dengan pengetahuan konten baik, tetapi mempunyai pengetahuan pedagogis yang kurang; (3) guru dengan pengetahuan konten kurang, tetapi mempunyai pengetahuan pedagogis yang baik; dan (4) guru dengan pengetahuan konten dan pengetahuan pedagogis yang kurang. Idealnya seorang guru harus masuk ke dalam kelompok (1), tetapi kenyataannya banyak yang belum bisa dikategorikan ke dalam kelompok tersebut.…”
Section: Introduction *unclassified